1979
DOI: 10.3186/jjphytopath.45.436
|View full text |Cite
|
Sign up to set email alerts
|

Rice ragged stunt virus, a new member of plant reovirus group.

Abstract: Rice ragged stunt virus (RRSV), which has been prevalent in South and Southeast Asia since 1977, caused typical symptoms on japonica rice, such as Kinmaze and Mihonishiki. However, barley, oat, wheat and maize, which had been known as hosts of rice black-streaked dwarf virus (RBSDV), were not susceptible to RRSV. The infected japonica rice developed symptoms of stunting, leaf twisting and vein swelling, that were identical to those caused by RBSDV.Other typical symptoms, such as nodal branching and ragged leav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
1

Year Published

1980
1980
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 1 publication
0
7
1
Order By: Relevance
“…Our results differ from those of Shikata et al [6]; the following may be among the possi ble reasons. The isometric particles in figure 1A of Shikata et al [6], measuring 35 nm in diameter, seem clearly to not be those of RRSV and possibly belong to a contaminant virus.…”
contrasting
confidence: 56%
See 1 more Smart Citation
“…Our results differ from those of Shikata et al [6]; the following may be among the possi ble reasons. The isometric particles in figure 1A of Shikata et al [6], measuring 35 nm in diameter, seem clearly to not be those of RRSV and possibly belong to a contaminant virus.…”
contrasting
confidence: 56%
“…A B-spiked particle resembling the subviral particles (SVPs) of fijiviruses and also the complete particle of cytoplasmic polyhedrosis viruses (CPVs) has been found [4][5][6][7]; but a particle corresponding to the typical fijivirus double-shelled virion could not be detected in one report [7], while in others [5,6] such a particle was not con vincingly demonstrated. Moreover, Shikata et al [6] found particles of very diverse appear ance, ranging in diameter (as measured on the illustrations) from 35 to 75 nm, all supposedly being particles of RRSV imaged under vari ous conditions. One report [4] suggests that complete virions may have been observed in thin sections of RRSV-infected vector insects.…”
mentioning
confidence: 99%
“…Rice ragged stunt Oryzavirus (RRSV) has an icosahedral particle of approximately 65nm in diameter, possesses a genome consisting of 10 double-stranded (ds) RNA segments and has been shown to be a member of the family Reoviridae2, 8,14 Nucleotide sequence information is an essential requirement to examine the interviral relationship and to analyze gene functions at molecular level. To date, the complete nucleotide sequence has been determined for genomic segments of some phytoreoviruses and Fujiviruses.…”
Section: Introductionmentioning
confidence: 99%
“…Reoviridae, is an icosahedral particle approximately 65 nm in diameter, possessing a genome consisting of 10 dsRNA segments with Mrs ranging from 0-76 × 106 to 2.48 × 106, and includes an RNA-dependent polymerase capable of transcribing the dsRNA genome into mRNAs (Shikata et al, 1979;Kawano et al, 1983Kawano et al, , 1984Boccardo et al, 1984;Lee et al, 1988;Uyeda et al, 1987Uyeda et al, , 1990). …”
Section: Rice Ragged Stunt Virus (Rrsv) a Member Of The Plantmentioning
confidence: 99%